Evidence for single top-quark production in the s-channel in proton–proton collisions at √s=8TeVwith the ATLAS detector using the Matrix Element Method - Alconada Verzini, María Josefina (2016)
This Letter presents evidence for single top-quark production in the s-channel using proton–proton collisions at a centre-of-mass energy of 8TeVwith the ATLAS detector at the CERN Large Hadron Collider. The analysis is performed on events containing one isolated electron or muon, large missing transverse momentum and exactly two b-tagged jets in the final state. The analysed data set corresponds to an integrated luminosity of 20.3fb−1. The signal is extracted using a maximum-likelihood fit of a discriminant which is based on the matrix element method and optimized in order to separate single-top-quark s-channel events from the main background contributions, which are top-quark pair production and Wboson production in association with heavy-flavour jets. The measurement leads to an observed signal significance of 3.2 standard deviations and a measured cross-section of σs=4.8 ±0.8(stat.)+1.6−1.3(syst.)pb, which is consistent with the Standard Model expectation. The expected significance for the analysis is 3.9 standard deviations.